Strategi Meningkatkan Imunitas Tubuh melalui Pola Hidup Seimbang dan Kesehatan Mental pada Masa Pandemi COVID-19 - Avrizha Adji Wibowo; Adrian Herli Fernandaez; Muhammad Adi Nugroho; Aan Riski Susanto; Liss Dyah Dewi A (Student Research Journal, 2024)
The COVID-19 pandemic has posed major challenges to global health, not only in physical aspects but also mental health. This article discusses strategies for increasing body immunity through a balanced lifestyle and optimal mental health during the pandemic. This research reviews various factors that contribute to immune system strength, including nutrition, physical activity, adequate sleep, as well as stress management and mental health. It also emphasized the importance of a holistic approach that integrates a healthy lifestyle and psychological well-being to strengthen the body's defenses against infection.